An Emergency Medicine Milestone-Based Simulation Curriculum: Acute Ischemic Stroke - Danielle Turner-Lawrence; Bophal Sarha Hang; Payal Shah; Kelly Levasseur (Association of American Medical Colleges, 2019)
Introduction The emergency medicine (EM) resident's ability to make independent decisions in the setting of acute ischemic stroke has been reduced as a result of the involvement of multidisciplinary teams. This simulation was created to give EM residents the opportunity to independently manage the early stages of ischemic stroke and its complications. Methods A solo learner was presented with a 55-year-old male with complaints consistent with an acute stroke. The resident had to calculate stroke severity; coordinate hospital resources; discuss risks, benefits, and alternatives to thrombolysis; and deal with subsequent complications. The learner had to keep a broad differential for sudden change in mental status and consider alternative interventions. Strategies to decrease intracranial pressure needed to be implemented while obtaining neurosurgical consultation. Debriefing included discussion of expected actions in the context of the Accreditation Council for Graduate Medical Education (ACGME) milestones. Residents' review of their video performance added additional self-reflection. Results A total of 69 PGY 3 EM residents independently participated in this simulation over a 5-year period. Thirty-two completed a postsimulation evaluation. Nearly all learners felt that this case reflected an actual patient encounter and increased their confidence in managing stroke. The milestone-based feedback tool was completed with all learners. Anticipated actions linked to Level 1 and 2 milestones were regularly achieved while acquisition of Level 3 and 4 actions varied. Discussion Case actions were uniquely characterized by the ACGME milestones, which helped to delineate learners' knowledge gaps and provided concrete areas for improvement.